PENGARUH SENAM KAKI DIABETES TERHADAP TINGKAT SENSITIVITAS KAKI DAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS DI KELURAHAN BANYURADEN GAMPING SLEMAN - Rusandi, Dedi; Prabowo, Tri; Adinugraha, Tetra Saktika (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: High blood glucose level will lead to macrovascular complication that will subsequently causes neuropathy. One management technique that can prevent neuropathy in lower part extremity is by practicing diabetic foot exercises which can improve blood circulation. Objective: To investigate the effect of diabetic foot exercise on the level of foot sensitivity and blood glucose level in people with diabetes mellitus in Banyuraden Gamping Sleman. Methods: This was a quasi-experimental research with pre- and post-test controlled groups. This research was conducted in Banyuraden Gamping Sleman with 32 subjects as samples, 16 subjects were in the intervention group and the rest were in the control group. Researcher used foot exercise procedure instrument; cotton, brush, and needle to measure the foot sensitivity; and glucometer to test the blood glucose level. Data were then analysed with independent sample t-test. Result: The result showed that there was significant difference in the foot sensitivity between the intervention and the control groups, p=0.010 (p<0.05), while the blood glucose level difference showed pvalue 0.039 (p<0.05). Conclusion: Diabetic foot exercise had a significant effect on the level of foot sensitivity and blood glucose level in people with diabetes mellitus in Banyuraden Gamping Sleman. Key words: Foot Exercise, Foot Sensitivity, Blood Glucose Level, Diabetes Mellitus